REPORT OF COMMITTEE ON MANAGEMENT ACCOUNTING. - Brummet, R. Lee; Crossman, Paul T.; Pressler, Stanley A.; Weltmer, W. Keith; Welsch, Glenn A. (The Accounting Review, 1959)
Abstract In January 1957, the Executive Committee of the American Accounting Association appointed the first committee on management accounting; the primary charge being "to clarify just what is meant by the term management accounting. In recent years there has been a growing awareness of the potential utilization of accounting data by management for internal purposes. At the same time there has been an increasing recognition of the limitations of accounting as it exists today in meeting these needs. Management accounting is the application of appropriate techniques and concepts in processing the historical and projected economic data of an entity to assist management in establishing a plan for reasonable economic objectives and in the making of rational decisions with a view toward achieving these objectives. It includes the methods and concepts necessary for effective planning, for choosing among alternative business actions and for control through the evaluation and interpretation of performance. Management accounting concepts are especially important in that they deal with the fundamentals of maximizing return on investment, a primary objective of the business entity. This is especially true in the field of marketing where the broad and complex problems of pricing, methods of distribution, marginal cost and product mix must be met and solved.